Fundamentalism, complexity and inclusion. Contribution for na inclusive education - Rodrigues, David (2020)
This article highlights the main aspects of a fundamentalist thinking and the inadequacy of the solutions for the problems of complex societies, and increasingly complex, as those we live in. Based on the distinction between fundamentalism and the theory of complexity, the author debates the concept of inclusion, detaching it from the perspectives that limit its meaning. Finally, he presents some lines of thought that may help to better understand and promote an Inclusive Education.